The Important Moderation Fatwa Contemporary and Ijtihad - Marling, Nashirul Haq (Yayasan Marwah Madani Riau, 2022)
Verify the eligibility of ijtihad, so that anyone who does not know the purpose, understands it and is able to access and know it, is not eligible for ijtihad. One of the most important principles and foundations that must be considered in applying the theory of sharia objectives in ijtihad and fatwas is the moderation approach. This study discusses